(untitled) (Journal of humanities and social sciences exploratio, 2025)
This research aims to deeply explore the rich cultural heritage of Heyuan City and promote the revitalization and development of its cultural tourism industry through the integration of culture and tourism. As one of the important birthplaces of Lingnan culture, Heyuan has a profound historical accumulation and unique natural heritage resources, but its tourism development and publicity efforts have long lagged behind its cultural value. Therefore, this study systematically combs the cultural resources of Heyuan from multiple dimensions such as historical culture, characteristic cultural tourism, and natural heritage, and combines the theoretical and practical experience of cultural and tourism integration at home and abroad to propose a series of operable integration development paths.The study finds that the cultural resources of Heyuan not only cover rich contents such as the culture of Zhao Tuo, the history of Qin conquering Nanyue, and stone carving art, but also have unique ecological resource advantages such as Danxia landform and Wanlu Lake. By strengthening cultural and tourism interactions with relevant cities, such as linking with Guilin on the Lingqu culture and dialoguing with Mount Tai on the stone carving culture, the cultural influence and tourism attractiveness of Heyuan can be significantly enhanced. This research is expected to provide theoretical support and practical guidance for the development of Heyuan’s cultural and tourism industry, help it achieve high-quality development, and at the same time provide useful reference for other similar regions.